EFL TEACHERS’ PERCEPTIONS ON THE CHANGES IN THE 2013 CURRICULUM AT JUNIOR HIGH SCHOOLS IN MARTAPURA - Devie Dian Nisrina (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research is to examine the extent of the EFL teachers’ perceive and describe their perceptions on the changes in the 2013 curriculum at junior high schools in Martapura. This research uses a survey design with techniques used to collect data are questionnaires and documentation. In this research, random simple sampling is used and the number of respondents are 17 EFL teachers at junior high schools in Martapura. The result of this research has found that EFL teachers’ indicates positive about the 2013 curriculum. The extent of the EFL teachers’ perceive on the changes in the 2013 curriculum in the highest percentage is EFL teachers’ perceive in learning resources and education facilities that have 92,4%, the medium percentage is student centered learning that have 83,5%, and the low percentage is evaluation and assessment that have 76,8%. Appropriate with the low percentage in evaluation and assessment, it was also found that EFL teachers’ has perception that they still lack with the assessment system in the 2013 curriculum.